Adoption of E-Wallets among Students: Trust and Social Influence in E-Commerce - Jihad, Hafsha Alia; Mustofa, Rochman Hadi (Universitas Batanghari Jambi, 2024)
E-commerce introduces the e-wallet payment transaction system as an innovation that offers convenience and security for consumers in purchasing goods and services online. This research explores the influence of trust in social environments in fostering the intention of students in Central Java, Indonesia, to use e-wallets, utilizing technology theories such as the Technology Acceptance Model (TAM). A quantitative study was conducted through an online survey among students. Purposive sampling was employed as the sampling technique, and data were analyzed using the Partial Least Squares (PLS) approach within Structural Equation Modeling (SEM) analysis. The study found that the factors of trust and social influence significantly impact the intention to use e-wallets, with trust even playing a supportive role in fostering this intention alongside other factors. These findings will assist service providers in enhancing e-wallet services with new innovations tailored to user needs.